Konsep mimpi dalam perspektif psikologi Islam: Studi komparasi psikologi Islam dan psikologi Barat - Yuminah, Yuminah (Jurnal Psikologi Islam, 2018)
This article aimed to uncover the phenomenon of dreams through Islamic psychology perspective. The discussion focused on the essence of dreams psychologically both in general psychology and Islamic psychology. The discussion in this article also talked about how the position and the quality of dreams in accordance with what is described in the Qur’an and hadiths. There are three conclusions in this article. First: dreams in Islamic psychology are believed in addition to the mental and psychological aspects, also related to inspiration or revelation that function as good news for the servant, the test of faith, pieces of some future events to prepare the individual to face when it comes and grow the spirit of struggle. Second: the position of dreams in Islamic psychology affects the individuals’ physical and psychological condition. Third: the quality of dreams in Islamic psychology also affects individuals’ mental and behavior. Keywords: Dreams, Islamic Psychology, Western Psychology.